add and subtract by first simplifying each radical and then combining any like radical terms. assume that all variables represent positive real numbers

Thank you for the opportunity to help you with your question!

(sqrt64x)+(sqrt25x)-12sqrtx

= √(64) x + √(25x)- 12 √x

= √8*8*x + √5*5*x - 12 √x

= 8 √x + 5 √x - 12 √x

= (8+5 - 12) √x

= 1 √x

= √x..................................ANSWER

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up